Internet Olympics: The Internet's Role at the 1998 Nagano Winter Olympic Games - Agoston, T. C.
Since the 1996 Summer Games in Atlanta, the Internet has been an integral medium for numerous Olympic and sports constituencies. The XVIII Olympic Winter Games were held in Nagano, Japan, February 7-22, 1998. Starting in 1997, the official games' Web site (http://www.nagano.olympic.org) distributed timely results and a continuously updated flow of information about the competitors, events, and other related useful and interesting subjects. In accordance with the growing popularity of sports Web sites, this noncommercial site generated record traffic from a worldwide, multilingual audience. The Organizing Committee for the XVIII Olympic Winter Games, Nagano 1998 (NAOC) owns the site; IBM, the official Worldwide Information Technology Partner for the Nagano Olympic Winter Games, provided design services, content hosting, implementation, and management of the site's technology infrastructure. This paper is a case study of the official Web site as an alternative channel which provided the "Olympic experience" on the Internet and delivered multilingual (English, Japanese, and French) multimedia content to the online Olympic communities.